Effectiveness of social support with adolescent's self-acceptance in post-divorce parents - Merri Hafni (INSPIRA: Indonesian Journal of Psychological Research, 2020)
The study aims to identify the effectiveness of social support to self-acceptance in adolescent post-divorce parents. The samples in this study were 40 students of SMA Al-Ulum Medan. The technique of sampling data was to use purposive sampling taken using the criteria of adolescents who are divorced parents and obtained from documentation from the school. The data collection method was the Social Support Scale and the Self-Acceptance Scale. Analyze the data using Product Moment correlation. The findings showed a significant association between social support and self-acceptance, with the coefficient is 0.875 and p-value< 0.001. The results showed that social support contributes to self-acceptance in 76.3%. That was, there were still 23.7% of other factors not studied in this study. The results showed that social support strongly influenced adolescents to accept their parents' divorce conditions.